2020
DOI: 10.7759/cureus.6932
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetic Patients Adherence Towards Their Medications

Abstract: Given that type 2 diabetes mellitus (T2DM) has become a common noncommunicable disease that can begin in early life and has a significant effect on the quality of life, it is important to address treatment adherence. While various factors contribute to the development of T2DM, the primary cause is linked to unhealthy eating and lack of physical activity. Adhering to healthy eating and physical exercise is not generally well tolerated by patients with diabetes, and pharmacological treatments are often necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…It is plausible that the level of health literacy, in regards to DM in Jeddah, is exceptionally high. A comparison of the studies measuring the level of knowledge about DM conducted in Jeddah [23] and adjacent areas, such as Al Riyadh [35], Makkah [36], Kuwait [37], and Al Ismailia in Egypt [38], showed that patients in Jeddah had more knowledge about DM, which lends support to this hypothesis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It is plausible that the level of health literacy, in regards to DM in Jeddah, is exceptionally high. A comparison of the studies measuring the level of knowledge about DM conducted in Jeddah [23] and adjacent areas, such as Al Riyadh [35], Makkah [36], Kuwait [37], and Al Ismailia in Egypt [38], showed that patients in Jeddah had more knowledge about DM, which lends support to this hypothesis.…”
Section: Discussionmentioning
confidence: 64%
“…These can be categorized into three major categories: the medical status [11], personal characteristics of the particular patient [22], and the agreed-upon therapeutic plan and medical encounter [9]. The personal characteristics contain the demographic data [22], forgetfulness [23], and personal beliefs [24]. The number of medications, complexity of the regimen, side effects, cost, and lack of trust in treatment efficacy are under the umbrella of the therapeutic plan and medical encounter [25].…”
Section: Introductionmentioning
confidence: 99%
“…This shows the importance that these people give to medication treatment, probably due to potential influences from the hospital-focused model. It is remarkable that another research (17) carried out in the state of Paraíba, showed a similar result, despite involving a different socioeconomic reality, considering that the adherence could be affected by different traditions, costumes, and environmental factors between societies and regions (18) .…”
Section: Variablesmentioning
confidence: 69%
“…Uma pesquisa nos Centros de Atenção Primária à Saúde de algumas cidades da Arábia Saudita mostrou que 62,3% não medem regularmente os níveis de glicemia 20 , corroborando com os resultados que tivemos neste estudo, onde apenas 16,7% seguiram as recomendações sobre a avaliação dos níveis de açúcar no sangue diariamente nos últimos sete dias.…”
Section: Discussionunclassified